DAMPAK STRUKTUR KEPEMILIKAN SAHAM MANAJERIAL PADA RETURNS DAN RISIKO OBLIGASI PERUSAHAAN - Setiyono, Setiyono (Jurnal Akuntansi dan Keuangan Indonesia, 2006)
The purpose of research is to analyze an impact of managerial stock ownership structure on corporate bond returns. It is assumed that the change in managerial stock ownerships can influence managers ’attitudes toward risk. So it is hypothesized that the change in managerial stock ownerships can influence corporate bond returns. This study suggested that there is a significant impact of managerial ownership structure on corporate bond returns. In 1998 -1999 time series cross-section of 31 corporate bonds that were listed on Surabaya Stock Exchange, I've found evidence of a significant non-monotonic relationship between managerial stock ownership and corporate bond returns. Bond returns first increase, then decrease, and finally rise slightly as ownership by manager rises. There is also weak evidence of a non-monotonic relationship between managerial stock ownership and firm leverage. This study finds a positive relation between managerial stock ownership and leverage up to 19.9 percent ownership level. When ownership increases more (over 19.9 percent), however, the relationship becomes negative. This empirical evidence indicates that greater managerial ownership gives managers an incentive to decrease risk by using low level of debt.